Evaluation of healthy lifestyle program among Malaysian adolescents living in day-school hostels - Teng, Chian Yi (2016)
This study aimed to evaluate the Healthy Lifestyle Program (Program Cara Hidup Sihat) among Malaysian adolescents living in day-school hostels. This study was conducted in 2012 to 2014 and one hundred schools (50 intervention and 50 control schools) were randomly selected based on urban to rural ratio in six regions in Malaysia. A total of 4277 Form One respondents (Intervention group: n=1885; Control group: n= 2392) participated in this study in 2012. Quantitative data were gathered at three time points, namely Pre-Intervention (Year 2012), Post-Intervention I (Year 2013) and Post-Intervention II (Year 2014) using a cluster randomized controlled trial. Intervention was conducted at two phases, namely Phase I intervention and Phase II intervention; whereby at Phase I, a four-month intervention was conducted while at Phase II, a six-month intervention was conducted among intervention respondents. Intervention schools received intervention while control schools received none. The school teachers in the intervention group used ten topics of the modules of Healthy Eating and Be Active among Teens (HEBAT) to educate the intervention respondents. At Phase I intervention, the HEBAT module (Phase I) consisted of four topics which introduced the concept and basic knowledge of healthy eating and active living, while at Phase II intervention, the HEBAT module (Phase II) consisted of six topics which trained intervention respondents to develop healthy lifestyle skills. This enabled the application of knowledge learned in the first phase of intervention among the intervention respondents. Each topic of HEBAT modules consisted of teaching guidelines, topic notes or power point slides, goal card, program feedback and tutorial forms. Moreover, each topic comprised two main learning objectives with various interactive learning activities. The UPM research team allocated one month for teachers to introduce one topic of HEBAT modules to the intervention respondents. One topic of HEBAT modules took one hour to deliver its content to the intervention respondents. After Phase I of intervention (four months), the UPM research team went to each school to collect data (Post-Intervention I) and after Phase II of intervention (six months), the UPM research team went to each school to collect data (Post-Intervention II). Assessment of the effectiveness of the Healthy Lifestyle Program was assessed using two evaluation components namely, process evaluation and impact evaluation. Attendance lists, tutorial and program feedback forms in the intervention group were used in process evaluation. The Knowledge, Attitude and Practice on Healthy Lifestyle Questionnaire, Eating Behaviours Questionnaire, Eating Attitudes Test-26, 24-hour dietary and physical activity recall, Physical Activity Questionnaires for Children, Body Weight Status Perception Questionnaire, Contour Drawing Rating Scale and Depression, Anxiety and Stress Scale were used in impact evaluation to determine knowledge, attitude and practice on healthy lifestyle, dietary practices, disordered eating behaviour, physical activity, body image and psychological distress of respondents. Anthropometric measurements were measured to determine the body composition (body weight status, waist circumference and body fat percentage) of respondents. A total of 4277 Form One respondents participated in this study, given an overall response rate of 82.5%. The mean age of the intervention group (n= 1885) was 12.98 (95% C.I.: 12.97, 12.99) years while for the control group (n= 2392) was 12.97 (95% C.I.: 12.96, 12.98) years. A majority of the respondents were female, Malay and from rural area in both groups. Almost 50.0% of the intervention respondents attended all topics of HEBAT modules and about 35.0% of the intervention respondents submitted all topics of tutorial and program feedback forms. There was 99.2% of the intervention respondents satisfied with the program sessions and agreed the sessions were interesting, easily understood and well-liked. After the program, the intervention group had higher knowledge, attitude and practice on healthy lifestyle; total energy, macronutrient and micronutrient intakes (except niacin and iron intakes); lunch, dinner and morning tea consumptions; physical activity; correct perception of actual body weight status; and percentage of thinness than their control counterparts. Niacin and iron intakes; supper consumption; breakfast, lunch, dinner and overall skipping behaviours; low physical activity level; incorrect perception of actual body weight status; depression; height; and percentage of overweight were lower in the intervention group than their control counterparts. However, there was no difference in breakfast and afternoon tea consumptions; snacking behaviors; disordered eating, total daily energy expenditure, percentage of body size satisfaction, stress and anxiety, BMI-for-age, waist circumference and body fat percentage between groups. In conclusion, the Healthy Lifestyle Program could promote healthy lifestyle effectively among Malaysian adolescents.